A computational study of MoS2 for band gap engineering by substitutional doping of TMN (T = transition metal (Cu), M = metalloid (B) and N = non-metal (C)). (13th April 2021) - Tayyab, Muhammad; Hussain, Akhtar; Asif, Qurat ul Ain; Adil, Waqar; Nabi, Shafqat; Rafiq, Nouman; Ahmed, Basharat
Abstract: Tunable electronic properties of two dimensional Molybdenum disulfide (MoS2 ) make it a potential material. In this study, we inspect electronic and structural properties of TMN-doped MoS2 (T = Transition metal (Cu-copper), M = Metalloid (B-boron) and N = Nonmetal (C-carbon)) by using first principles DFT (density functional theory) calculations. Cu is substituted by Mo with varying concentration, which ranges from 2.08 to 8.33%, whereas B and C are replaced by S atoms with varying concentration of 2.08 to 4.16%. The substitutions result into significant variations in electronic and structural properties of MoS2 . Moreover, the importance of substitutional site has been elaborated. The substitution of these impurities, variation in concentration and the replaced sites of MoS2 cause to modify the structure and energy gaps. Resulting bandgap fluctuates remain between 0.16 eV to 0.48 eV relative to 1.95 eV of pristine MoS2 . The PDOS calculations show good bonding relation among the host MoS2 and the foreign impurity TMN. Therefore, substitution of impurities gives the opportunity to vary the bandgap as required for its valuable applications as semiconducting materials.